The effects of countercyclical fiscal policy: Firm-level evidence from temporary consumption tax cuts in Turkey - Florian Misch; Atılım Seymen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
The paper investigates the effects of temporary consumption tax cuts using firm-level data. As part of its countercyclical measures implemented during the recent global economic crisis, Turkey temporarily lowered consumption taxes on selected durables. Using data on the change of sales of firms that benefited from this measure and of those that did not over different periods, we perform a difference-in-difference analysis where we also control for various unobservable effects including sector-specific shocks to address potential endogeneity. We find positive and robust effects of consumption tax cuts on the change of firm sales which is consistent with theoretical predictions.
urn:nbn:de:bsz:180-madoc-328933
Keywords: E32; E62; H20; 330; countercyclical fiscal policy; consumption tax cuts; firm-level data